ANALISIS PENERAPAN METODE PENCATATAN DAN PENILAIAN PERSEDIAAN BARANG DAGANG BERDASARKAN PSAK NO 202 PADA ASTRA MOTOR KOLAKA - Hardilla, Hardilla; Sabarudin, Sabarudin; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
The Research Was Conducted By Hardilla, With Student Id Number 211830897, Under The Title “Analysis Of The Application Of Merchandis Inventory Recording And Assesment Methods At Astra Motor Kolaka”. The Thesis Advisor Is Sabaruddin, SE.,M.M.,Ak.,C.FA And The Second Advisor Is Surianto Ilham, SE.,M.Acc.,Ak.,CA This Study Aims To Analyze The Method Of Recording And Assessing Merchandise Inventory At Astra Motor Kolaka And Assess Its Compliance With Financial Accounting Standart Statements (Psak) No. 202. The Research Method Used Is A Desriptive Qualitative Approach With Data Collection Techniques Through Interviews, Observations, And Doucumentation. The Results Of The Study Indicate That Astra Motor Kolaka Still Applies A Conventional Inventory Recording System That Tends To Resemble The Periodic Method And Has Not Used A Standard Inventory Valuation Method Such As Fifo, Or Average. This Shows That The System Used Is Not Fully In Accordance With The Provisions Of Psak No. 202. The Application Of This Inappropriate Method Has The Potential To Affect The Accuracy Of The Presentation Of The Company’s Finansial Statements. Therefore, It Is Recomended That The Company Immediately Evaluate The Inventory Recording And Valuation System To Comply With Applicable Accounting Standards.